Nurturing the older brain and mind [ - Greenwood, Pamela M. , 1947-; Parasuraman, R. (MIT Press, 2012)
Although our physical abilities clearly decline as we age, cognitive decline in healthy old age is neither universal nor inevitable. This book shows that scientific research does not support the popular notion of the inexorable and progressive effects of cognitive aging in all older adults. It reports that many adults maintain a high level of cognitive function into old age and that certain experiential and lifestyle factors?including education, exercise, diet, and opportunities for new learning?contribute to the preservation of cognitive abilities. Many popular accounts draw similar conclusions and give similar lifestyle advice but lack supporting scientific evidence. This book reviews research on cognitive and brain aging. It shows that even the aged brain remains capable of plasticity?the ability to adapt to and benefit from experience?and it summarizes evidence that brain plasticity is heightened by certain types of cognitive training, by aerobic exercise, and by certain diets. The book also reports on the somewhat controversial use of estrogen and cognition-enhancing drugs, on environmental adaptations (including ?virtual assistants?) that help older adults ?age in place,? and on genetic factors in cognitive aging. The past twenty years of research points to ways that older adults can lead rich and cognitively vital lives.